RPGR gene therapy presents challenges in cloning the coding sequence - De La Camara, Cristina Martinez-Fernandez (Expert Opin Biol Ther, 2020)
INTRODUCTION: Currently, there are three Phase I/II clinical trials based on gene therapy ongoing to test different AAV.RPGR or deleted RPGR vectors on patients affected by X-linked retinitis pigmentosa. These three vectors differ in the adeno-associated viral (AAV) vector capsid used, and the coding sequences: two contain codon optimized versions of RPGR which give the full-length protein, whilst the third uses a wild-type sequence that contains a large deletion encoding part of the functional domain of the RPGR protein. AREAS COVERED: This review approaches the different studies that have led to the initiation of three different clinical trials for RPGR related X-linked retinitis pigmentosa. EXPERT OPINION: The development of a gene therapy vector to deliver a normal copy of the RPGR gene into the photoreceptors has presented a challenge for the scientific community. The instability of its sequence and the fact that its function is not well understood can lead to the production of a nonfunctional or deleterious protein for the human retina. Since the RPGR protein undergoes post-translational glutamylation in the protein domain that may be particularly affected by gene instability, a functional assay of glutamylation is essential to verify the correct coding sequence.